EVOLUTION OF SCIENTIFIC VIEWS ON THE ESSENCE OF THE CONCEPT OF "PRODUCTIVE POTENTIAL" AND ITS CLASSIFICATION - MAZUR, Dmytro; MAZUR, Oleksandr; MAZUR, Halyna; STRAKHNITSKYI, Yaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the essence of the concept of "production potential" and its classification in order to increase the efficiency of economic activity. The evolution of the scientific understanding of the term "potential" is studied. The importance of studying the problem of the essence of potential and its assessment is determined, revealing the presence of significant differences in defining the essence of the concept of "potential" itself, its place among other economic categories. The study reveals the understanding of "production potential of an enterprise", which is a basic element of an enterprise, uniting goals, driving forces and sources of its development. The essence of potential, which is a dynamic category that is revealed only in the process of its use, is revealed. The use of potential, which is accompanied by its growth, and the processes of application and increase of potential, which are constant and complementary, are considered. The article defines the most complete definition of production potential as the ability of an enterprise to use resources, available and hidden opportunities in a dynamic market environment in order to implement statutory goals and objectives. The value of the enterprise potential, which consists in creating new value, has been determined. It has been found that the presence and application of any type of potential to one degree or another determines the result of the enterprise’s activities. The structure of the enterprise potential has been proposed, taking into account its objective and subjective components. This study presents the characteristics of the production potential of an industrial enterprise. The study considered the classification of production potential in terms of various characteristics that exist and are used in the economy, by level of hierarchy (individuals of micro-, meso- and macroeconomic levels), by sectoral characteristic, by scale of management, by form of ownership, by financial and economic status and many other characteristics. Based on the analysis of theoretical approaches to the definition of the understanding of production potential, the author’s concept was formed. The authors of the article investigated that production potential is a complex of perspectives of different technical and socio-economic systems that are closely interconnected and interdependent, and also ensure the implementation of effective operational and strategic activities of the enterprise.